Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.9745/ghsp-d-16-00312
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Neonatal Mortality of Newborn Infection Management at Health Posts When Referral Is Not Possible: A Cluster-Randomized Trial in Rural Ethiopia

Abstract: Health Extension Workers (HEWs), in general, properly provided antibiotic treatment of possible severe bacterial infections in newborns at the health post level. But only about half of newborns estimated to have infections in the intervention area received treatment by HEWs, and home visits and referrals declined in the final months of the study. Cluster-level analysis suggests a mortality reduction consistent with this level of treatment coverage, although the finding did not reach statistical significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 22 publications
4
34
0
Order By: Relevance
“…Bacterial infection, which is called as Possible serious bacterial infection (PSBI) [1][2][3][4], is a cause for an estimated number of 600,000 neonatal deaths per year [2], accounting for approximately 23% of neonatal deaths, yet as high as 50% in low-income settings [5,6]. Its incidence ranges from 5.5 cases/1,000 live births for blood culture-confirmed infections, to 170 cases/ 1,000 births for clinically diagnosed cases in community-based settings [7]. In Ethiopia, also it is one cause of newborn mortality [8] and study showed 34.3% neonatal death was caused by neonatal infection [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacterial infection, which is called as Possible serious bacterial infection (PSBI) [1][2][3][4], is a cause for an estimated number of 600,000 neonatal deaths per year [2], accounting for approximately 23% of neonatal deaths, yet as high as 50% in low-income settings [5,6]. Its incidence ranges from 5.5 cases/1,000 live births for blood culture-confirmed infections, to 170 cases/ 1,000 births for clinically diagnosed cases in community-based settings [7]. In Ethiopia, also it is one cause of newborn mortality [8] and study showed 34.3% neonatal death was caused by neonatal infection [9].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these challenges, the World Health Organization [WHO] recommends management of possible serious bacterial infection among newborns at a community level when referral to hospital is not possible [2,10]. In Ethiopia, this community-based intervention for newborns with PSBI was started between 2008 and 2013, as a pilot to evaluate the impact of a regimen of intramuscular gentamicin and oral amoxicillin, given by health extension workers (HEWs) to newborns and young infants with signs of PSBI when referral is not possible [11] and was launched on March 2013. Currently, it is being implemented as one communitybased newborn care (CBNC) package and high impact newborn and child survival intervention [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire tools for baseline and endline surveys were adapted from the team's own, and others' previous work on the Integrated Management of Childhood Illness [28], iCCM [29], and CBNC [30]. The questionnaire instrument included modules regarding household, health posts and health centres, HEWs, health centre staff, WDA members, an observation and re-examination of the HEW assessing sick children, and district contextual factors (Table 2) [see additional files [1][2][3][4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…If appropriately trained and supported, this cadre can also treat severe infections of the newborn in a costeffective way within the Community-Based Newborn Care (CBNC) program that has been running since 2014 [6]. Although nearly all the HEWs throughout the country have been trained, relatively few sick newborns have been identified and treated [7]. Since 2011 a volunteer cadre called the Women's Development Army (WDA-also known as the Health Development Army or Women's Development Group) is active in promoting the use of health services [8,9].…”
Section: Introductionmentioning
confidence: 99%